The UK Northern region genetic register for familial adenomatous polyposis coli: use of age of onset, congenital hypertrophy of the retinal pigment epithelium, and DNA markers in risk calculations. Issue 5 (May 1991) - Burn, J; Chapman, P; Delhanty, J; Wood, C; Lalloo, F; Cachon-Gonzalez, M B; Tsioupra, K; Church, W; Rhodes, M; Gunn, A
Abstract : A polyposis register has been established in the Northern Region of England. A total of 48 families with 71 living affected subjects has been identified during the first three years of operation, a prevalence of 2.29 x 10(-5). Indirect ophthalmoscopy identifies the majority of gene carriers by showing multiple areas of congenital hypertrophy of the retinal pigment epithelium (CHRPE). The absence of this sign in families limits its value where a relative with CHRPE has not been identified. Combining eye examination with data on age of onset and linked DNA markers is highly effective in carrier exclusion; 38% of 528 first, second, and third degree relatives had their carrier risk reduced to less than 1 in 1000. Even with such assurance many subjects will request continued bowel screening at a reduced frequency. Little interest has been shown in prenatal diagnosis. The principal value of a genetic register with domiciliary nurse visiting is the reduction in early mortality among unrecognised gene carriers.